Identification of BAHD acyltransferases associated with acylinositol biosynthesis in Solanum quitoense (naranjilla) - Bryan J. Leong; Steven Hurney; Paul Fiesel; Thilani M. Anthony; Gaurav Moghe; Arthur Daniel Jones; Robert L. Last (Plant Direct, 2022)
Abstract Plants make a variety of specialized metabolites that can mediate interactions with animals, microbes, and competitor plants. Understanding how plants synthesize these compounds enables studies of their biological roles by manipulating their synthesis in vivo as well as producing them in vitro. Acylsugars are a group of protective metabolites that accumulate in the trichomes of many Solanaceae family plants. Acylinositol biosynthesis is of interest because it appears to be restricted to a subgroup of species within the Solanum genus. Previous work characterized a triacylinositol acetyltransferase involved in acylinositol biosynthesis in the Andean fruit plant Solanum quitoense (lulo or naranjilla). We characterized three additional S. quitoense trichome expressed enzymes and found that virus‐induced gene silencing of each caused changes in acylinositol accumulation. pH was shown to influence the stability and rearrangement of the product of ASAT1H and could potentially play a role in acylinositol biosynthesis. Surprisingly, the in vitro triacylinositol products of these enzymes are distinct from those that accumulate in planta. This suggests that additional enzymes are required in acylinositol biosynthesis. These characterized S. quitoense enzymes, nonetheless, provide opportunities to test the biological impact and properties of these triacylinositols in vitro.